Single opsin driven white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in Neuroscience, 2023)
Purpose Electroretinograms elicited by photopigment isolating white noise stimuli (wnERGs) in mice were measured. The dependency of rod- and cone-opsin-driven wnERGs on mean luminance was studied. Methods Temporal white noise stimuli (containing all frequencies up to 20 Hz, equal amplitudes, random phases) that modulated either rhodopsin, S-opsin or L*-opsin, using the double silent substitution technique, were used to record wnERGs in mice expressing a human L*-opsin instead of the native murine M-opsin. Responses were recorded at 4 mean luminances (MLs). Impulse response functions (IRFs) were obtained by cross-correlating the wnERG recordings with the corresponding modulation of the photopigment excitation elicited by the stimulus. So-called modulation transfer functions (MTFs) were obtained by performing a Fourier transform on the IRFs. Potentials of two repeated wnERG recordings at corresponding time points were plotted against each other. The correlation coefficient (r2repr) of the linear regression through these data was used to quantify reproducibility. Another correlation coefficient (r2ML) was used to quantify the correlations of the wnERGs obtained at different MLs with those at the highest (for cone isolating stimuli) or lowest (for rod isolating stimuli) ML. Results IRFs showed an initial negative (a-wave like) trough N1 and a subsequent positive (b-wave like) peak P1. No oscillatory potential-like components were observed. At 0.4 and 1.0 log cd/m2 ML robust L*- and S-opsin-driven IRFs were obtained that displayed similar latencies and dependencies on ML. L*-opsin-driven IRFs were 2.5–3 times larger than S-opsin-driven IRFs. Rhodopsin-driven IRFs were observed at −0.8 and − 0.2 log cd/m2 and decreased in amplitude with increasing ML. They displayed an additional pronounced late negativity (N2), which may be a correlate of retinal ganglion cell activity. R2repr and r2ML values increased for cones with increasing ML whereas they decreased for rods. For rhodopsin-driven MTFs at low MLs and L*-opsin-driven MTFs at high MLs amplitudes decreased with increasing frequency, with much faster decreasing amplitudes for rhodopsin. A delay was calculated from MTF phases showing larger delays for rhodopsin- vs. low delays for L*-opsin-driven responses. Conclusion Opsin-isolating wnERGs in mice show characteristics of different retinal cell types and their connected pathways.